Enhancing the scalability of the collaborative care model for depression using mobile technology. Issue 3 (7th August 2020) - Carleton, Kelly E; Patel, Urvashi B; Stein, Dana; Mou, David; Mallow, Alissa; Blackmore, Michelle A
Abstract: The collaborative care model (CoCM) has substantial support for improving behavioral health care in primary care. However, large-scale CoCM adoption relies on addressing operational and financial implementation challenges across health care settings with varying resources. An academic medical center serving socioeconomically and racially diverse patients implemented the CoCM in seven practices. A smartphone application was introduced to facilitate CoCM care management during depression treatment (app-augmented CoCM). App features included secure texting, goal/appointment reminders, symptom monitoring, and health education material. A nonrandomized convenience patient sample ( N = 807) was enrolled in app-augmented CoCM and compared with patients in standard CoCM ( N = 3, 975). Data were collected on clinical contact frequency, engagement, and clinical outcomes. App-augmented CoCM patients received more health care team contacts (7.9 vs. 4.9, p < .001) and shorter time to follow up compared with the standard CoCM sample (mean = 11 vs. 19 days, p < .001). App-augmented CoCM patients had clinical outcomes similar to the standard CoCM group (47% vs. 46% with ≥50% depression improvement or score <10), despite app-augmented patients having more prior depression treatment episodes. Further, the app-augmented group with greater app engagement demonstrated increased behavioral health appointment compliance, including more completed appointments and fewer no shows, and greater depression symptom improvement than those with less app engagement. App-augmented CoCM may improve patient engagement in treatment and provide opportunities to implement key CoCM elements without overburdening practice resources. CoCM sustainability and scalability in primary care may be enhanced by using this technology. Abstract : Socioeconomically and racially diverse minority patients showed more engagement in collaborative care for depression treatment when using a care management mobile app compared to patients not using the app.